Endovascular treatment of unruptured intracranial aneurysms with flow diverters: A retrospective long-term single center analysis. Issue 1 (February 2023) - Simgen, Andreas; Roth, Christian; Kulikovski, Johann; Papanagiotou, Panagiotis; Roumia, Safwan; Dietrich, Philipp; Mühl-Benninghaus, Ruben; Kettner, Michael; Reith, Wolfgang; Yilmaz, Umut
Purpose: The introduction of flow diverters (FDs) in 2007 greatly enhanced the treatment of intracranial aneurysms. Here, we present our long-term clinical experience in treating unruptured intracranial aneurysms with FDs. Methods: 107 patients with unruptured aneurysms and treated with an FD between 2010 and 2019 were retrospectively reviewed. Aneurysm occlusion, procedural complications, and clinical outcome were evaluated. Results: Angiographic follow-up was available for 93 patients with a mean long-term follow-up time of 28.4 ± 21.6 months. Additional coiling was performed in 15.1% of patients ( n = 14). Adequate aneurysm occlusion (Kamran grades 3 and 4) at long-term follow-up was achieved in 94.6% of patients ( n = 88). 3.2% ( n = 3) required endovascular retreatment since the last follow-up showed a lack of aneurysm occlusion (Kamran grade 0) due to a foreshortening of the FD. Incomplete opening of the FD and parent vessel occlusion was seen in 1.1% ( n = 1) and 3.2% ( n = 3) of patients, respectively. In-stent stenosis was observed in 57% ( n = 53) of cases at short-term follow-up and 22.6% ( n = 21) at long-term, which were moderate and asymptomatic overall. In-stent stenosis decreased significantly between short- and long-term follow-ups (31.4 ± 17.0% vs 9.7 ± 13.6%, respectively; p ≤ 0.001). Thromboembolic and hemorrhagic events occurred in 7.5% ( n = 7) and 1.1% ( n = 1) of patients, respectively. Good clinical outcome (modified Rankin scale: 0–2) was obtained in 97.8% ( n = 91) leading to an overall treatment-related morbidity of 2.2% ( n = 2). There was no procedural mortality. Conclusion: Our study shows that FD treatment of unruptured intracranial aneurysms is effective and safe with high occlusion rates and low rates of permanent morbidity at long-term follow-up.